Crise econômica e decisão de investimento em empresas brasileiras: o impacto do endividamento e restrição financeira - Boaro, Rayza Meleti (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation investigates the impact of financial constraints and indebtedness on investment decisions of publicly traded Brazilian companies during economic downturns. Utilizing a panel data econometric model, the study examines the relationship between variables such as leverage, sales growth, interest coverage ratio (ICR), return on assets (ROA), company size, and Tobin's Q, and corporate investment. The research is based on accounting data from Brazilian companies listed on B3, collected over a 12-year period (2010-2022). The results indicate that leverage has a significant negative effect on investments in unconstrained companies, while the negative relationship in constrained and highly leveraged companies did not show statistical significance. It is concluded that the relationship between financial constraints and investment is complex and depends on various company-specific and economic context factors. These results confirm previous studies on financial constraints, in which the findings for Brazilian companies are the opposite of the findings in developed companies. This fact leads to the proposal of the need to rethink the adequacy of financial theory in emerging economies, with poorly developed financial and capital markets.
Keywords: Restrição financeira; Endividamento; Investimento corporativo; Crise econômica; Financial constraints; Indebtedness; Corporate investment; Economic crisis; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis